Dismal Outcomes and High Societal Burden of Mitral Valve Regurgitation in France in the Recent Era: A Nationwide Perspective. Issue 15 (4th August 2020) - Messika‐Zeitoun, David; Candolfi, Pascal; Vahanian, Alec; Chan, Vincent; Burwash, Ian G.; Philippon, Jean‐François; Toussaint, Jean‐Manuel; Verta, Patrick; Feldman, Ted E.; Iung, Bernard; Glineur, David; Mesana, Thierry; et al.
Abstract : Background: Although US recent data suggest that mitral regurgitation (MR) is severely undertreated and carries a poor outcome, population‐based views on outcome and management are limited. We aimed to define the current treatment standards, clinical outcomes, and costs related to MR at the nationwide level. Methods and Results: In total, 107 412 patients with MR were admitted in France in 2014 to 2015. Within 1 year, 8% were operated and 92% were conservatively managed and constituted our study population (68% primary MR and 32% secondary MR). The mean age was 77±15 years; most patients presented with comorbidities. In‐hospital and 1‐year mortality rates were 4.1% and 14.3%, respectively. Readmissions were common (63% at least once and 37% readmitted ≥2 times). Rates of 1‐year mortality or all‐cause readmission and 1‐year mortality or heart failure readmission were 67% and 34%, respectively, and increased with age, Charlson index, heart failure at admission, and secondary MR etiology; however, the event rate remained notably high in the primary MR subset (64% and 28%, respectively). The mean costs of hospital admissions and of readmissions were 5345±6432 and 10 080±10 847 euros, respectively. Conclusions: At the nationwide level, MR was a common reason for admission and affected an elderly population with frequent comorbidities. Less than 10% of patients underwent a valve intervention. All subsets of patients who were conservatively managed incurred high mortality and readmissions rates, and MR represented a major societal burden with an extrapolated annual cost of 350 to 550 million euros (390–615 million US dollars). New strategies to improve the management and outcomes of patients with both primary and secondary MR are critical and warranted.